The incidence of dysphagia in diabetic patients - Boolkin, Lauren (My University, 2016)
This study was designed to examine the incidence of dysphagia in a group of fifty diabetic patients. The interrelationship between dysphagia and other complications of diabetes was examined. These included neuropathy, orthostatic dysfunction, renal dysfunction and respiratory disorders. Issues such as type of diabetes, patient age and age of onset were addressed. The utility and sensitivity of an interview schedule devised by the researcher was critically evaluated. Data were obtained through the administration of a standardized open-ended interview schedule coupled with an examination of the patients' hospital files. Results were interpreted and tabulated by the researcher. Results revealed that a significant proportion of diabetic patients are experiencing swallowing difficulties within all three phases of the swallow process. It is postulated that the cause of the dysphagia may be due to severe autonomic neuropathy and consequent vagal denervation. The highest incidence of dysphagia appeared to be amongst Type I diabetics who developed diabetes before the age of forty. The interview schedule was thus able to detect those patients experiencing dysphagia. However it was found to be unsuccessful in determining the severity of the problem. Clinical implications for both the Speech Therapist and the Medical team are discussed. Suggestions for future research are put forward.
A report on a study submitted to the Department of Speech Pathology, Faculty of Arts. University of The Witwatersrand, Johannesburg in Partial fulfilment of the requirements for the Degree of Masters of Arts in Speech Pathology, Johannesburg, 1998.
Keywords: Deglutition disorders.; Diabetes -- Patients.